A study on the potential of polystyrene lightweight aggregate in concrete - Fetra Venny Riza
This research comprised the effort to produce lightweight aggregate concrete from waste expandable polystyrene or also known as polystyrene foam that can be found easily around our neighborhoods as electronic packaging.